Pengaruh Kebijakan Dividen, Likuiditas dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Farmasi dan Riset Kesehatan Terdaftar di BEI Periode 2018-2024 - Tantri Nur Aisah; Eni Endaryati; Iwan Koerniawan (LPPM Universitas Sains dan Teknologi Komputer, 2026)
This study examines how dividend policy, liquidity, and profitability affect firm value within pharmaceutical and health research companies listed on the Indonesian Stock Exchange. Firm value is represented by Price to Book Value (PBV), while the independent variables consist of Dividend Payout Ratio (DPR), Current Ratio (CR), and Return on Assets (ROA). The population covers all firms in the sector, with 56 observations selected through purposive sampling. Data analysis is conducted using multiple linear regression supported by SPSS software. The findings indicate that, on a partial basis, DPR and CR do not exert a significant influence on PBV. In contrast, ROA demonstrates a positive and statistically significant effect, suggesting that profitability serves as a primary consideration for investors in evaluating firm value. Furthermore, the simultaneous test (F-test) reveals that DPR, CR, and ROA collectively have a significant impact on PBV, with a coefficient of determination (R²) of 47.9%. These results reinforce signaling theory, emphasizing that strong profitability performance sends a credible signal to the market in shaping firm value.